Evaluating The Effectiveness Of Anti-Smoking Messages On Knowledge About Health Effects, Negative Thinking And Behaviour Among Malaysians - Zawahir, Mohamed Shukry (2012)

(untitled)
Tobacco use has been identified as the leading cause of death and disability in the world. In Malaysia, overall (age ≥15 years) smoking prevalence of 23.2%, with male smoking rate is 44.6%. Among teenagers, 15% indicated as experimenters, another 8% confessed to being regular smokers. Smoking-related diseases had caused 35% of the death in Government hospitals in 2006. The Malaysian government launched a comprehensive national anti-smoking media campaign called “Tak Nak” in targeting at children, youth, women as well as smokers and the non-smokers.